Friedel Crafts Reactions Revisited: Some Applications in Heterogeneous Catalysis# - Lachter, Elizabeth R.; San Gil, Rosane A.S.; Valdivieso, Luis G. (Current Organic Chemistry, 2024)
Important organic reactions require the use of catalysts. The Friedel-Crafts reactions were discovered by Charles Friedel and James Mason Crafts in 1887. They are an essential catalytic process since they are widely applied in different areas such as fuels, cleaning, and pharmacological products. The reaction is usually carried out in the presence of Lewis acids or Brønsted acids in a homogeneous medium, with the nucleophilic aromatic substrate in excess. Although there is still work in the literature on the Friedel- Crafts reaction in a homogeneous medium using metal halides, the tendency is to replace these catalysts, which generate effluents that are harmful to the environment. Heterogeneous catalysts using solid acids show advantages over homogeneous catalysts, especially concerning separating products from the reaction medium, recycling, and reusing. This paper presents a mini-review focusing on the use of solid acids in Friedel-Crafts reactions.
Keywords: MOFs